EVALUATION OF MORPHOLOGICAL TRAITS OF BARLEY (Hordeum vulgare L.) VARIETIES IN DIFFERENT INTER-ROW SPACINGS AND NITROGEN RATES UNDER IRRIGATION - Isa, A.; Garba, A.A.; Sabo, M.U.; Fagam, A.S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
A field experiment was conducted over two consecutive cropping seasons, 2021/2022 and 2022/2023, at the National Root Crop Research Institute’s station in Vom, located in the Jos South Local Government Area of Plateau State (Longitude 8°53' E, Latitude 9º56' N) at an altitude of 1,217 meters above sea level. The aim of the study was to evaluate how different barley genotypes, inter-row spacing, and nitrogen application rates affect barley production. The experimental setup included three barley genotypes (Traveler, Zhana, and Arupo‘s’), four nitrogen levels (0, 80, 100, and 120 kg N ha-1), and three inter-row spacing configurations (20, 30, and 40 cm), organized in a split-split plot design with three replications. The findings indicated that the control treatment resulted in significantly fewer days to heading, with 49.00 days recorded in the 2021/2022 season and 49.30 days in 2022/2023 at a nitrogen application of 80 kg/ha-1. In contrast, the 120 kg N/ha treatment led to delayed heading in both years. However, both the control and the 120 kg N/ha-1 treatment resulted in significantly earlier flowering days at a 40 cm inter-row spacing during both seasons. The genotype Arupo's achieved the highest grain yields, reaching 1251.0 kg/ha in 2021/22 and 1876.4 kg/ha in 2022/23 at a 20 cm inter-row spacing, with the application of 120 kg N/ha-1. The study found significant interactions among the number of days to heading, flowering, physiological maturity, and grain yield concerning nitrogen levels, row spacing, and variety. In conclusion, the genotype Arupo's was the earliest to reach heading, flowering, and maturity, while also yielding the highest grain production in the 20 cm inter-row spacing with a nitrogen level of 120 kg/ha. It is recommended that farmers utilize the Arupo's genotype with a 20 cm inter-row spacing and 120 kg N/ha for optimal barley production.